Relationship between knowledge, attitude and practice towards adoption of improved varieties of pearl millet among farmers in North-Eastern Nigeria - Galadima, Mohammed (2019)
Agriculture remains the fundamental tool for economic growth, poverty reduction and enhancement of food security. In Africa, almost 70% of the population that are involved in agriculture are small-scale farmers, working on a small portion of land, on average of not more than 2 hectares of land. However, in Sub-Sahara Africa, Nigeria is one of the major pearl millet producing countries with an average annual production of 4.8 million tons. Indisputably, pearl millet production is mostly carried out in North-eastern region of Nigeria, although, it is often below the expected production, because of low level of adoption, resulting from inadequate level of knowledge, attitude and practice on the improved technology, coupled with the insurgency, which had displaced millions of farmers. Hence, farmers mostly relied on traditional production method. These situations craved for this research, which was designed to determine the relationships between knowledge, attitude, practice and adoption of improved varieties of pearl millet by farmers in North-eastern Nigeria. Specifically, the objectives were to: 1) determine the level of knowledge, attitude, practice and adoption; 2) determine the relationship between knowledge, attitude, practice and adoption and 3) determine the most contributing independent factors to adoption of improved varieties of pearl millet among farmers in North- Eastern Nigeria. Hence, various relevant literatures were reviewed to buttress the study. The study adopted quantitative, cross-sectional correlational design for the study. Purposive and systematic sampling technique were used to select (477) pearl millet farmers in North-eastern Nigeria. Primary data were collected by using validated and pilot tested self-report questionnaire. Descriptive, correlation and regression were used for the analysis. The data revealed that, (92.8 percent) of respondents were male and (91.9 percent) were married. About (72.6 percent) had a family size of (8-14 persons). Majority were middle aged, between (20-50) years and (78.80 percent) had only primary and secondary education. While, (56.6 percent) had no extension contact and (84.6 percent) were members of cooperative societies whereas, greater number about (62.8 percent) had experience between (11-20 years) in pearl millet production. More than half (74.9 percent) cultivates between 1.6 to 3.5 hectares of land. Respondents monthly income ranged between N10, 000 (USD 28.00) a n d above N30, 000 (USD 84.00) from pearl millet farming. Results on the level of knowledge revealed that, majority of respondent (91.6 percent) recorded high level of knowledge, attitude (81.9 percent) moderate level, practice (53.2 percent) recording High and adoption level 64.5 percent high among respondents. Results of the correlation analysis revealed positive significant relationship between knowledge, attitude, practice and adoption at (p<0.01). The findings of the Regression analysis further revealed that, knowledge and practice were significant towards adoption at p<0.05 determinants. From the outcome knowledge contributes with a (β= 0.283, p= 000). Whereas, practice contributes with a (β=0.493, p=000). Though, attitude was insignificant towards adoption as confirmed by its (β=0.047, p=0.623). Hence, adjusted R2 of 0.366 indicates that, knowledge and practice contribute 36.6% of variance towards adoption. The outcome of the decisions on the hypothesis tested showed that there was a direct positive relationship between knowledge and practice towards adoption. While the decision on the hypothesis concerning the contributing factors to adoption indicates that knowledge and practice have made a significant contribution to the adoption of improved varieties of pearl millet. While, attitude was not significant and thus, did not contribute. The study concluded that knowledge, practice and adoption level among respondents was high and attitude was moderate. Results of the correlational analysis revealed that, positive significant relationship existed between knowledge, attitude, and practice towards adoption. While, the regression results revealed that, knowledge and practice contribute more towards adoption whereas, attitude did not contribute. Hence, practice had the highest contribution towards adoption with a Beta value of .493. Thus, based the study implication, the study suggests that, farmers should be encouraged towards developing positive attitudes in the cultivation of improved pearl millet in the study area. Government and other relevant agencies should provide farm inputs, funds, access to improve seeds at affordable prices, available, and as well as provide adequate support towards extension mechanism, in their efforts to intensify farmers level of awareness on the use of improved pearl millet technologies. More extension agents be employed by the government to improve farmer-extension agents’ relationship in North-Eastern Nigeria. Further studies be conducted, considering other factors such, as the cultural belief and practices, insurgency, farmers’ level of mechanization which might had been considered and could play an important role in influencing adoption among farmers in North-eastern Nigeria.